The process of organisation change : case studies of the implementation of TQM within four medium-sized manufacturing organisations : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Business Studies in Business Studies at Massey University - Todd, Susan (Massey University, 1995)
The aim of this study was to understand the processes involved with the implementation of TQM within manufacturing organisations. A major contention being that TQM implementation constitutes an organisational development intervention, the implementation of which constitutes a process of planned organisational change. The study suggests that TQM implementation is not a simple and straight forward activity as suggested within the literature. Instead it is a complex and ongoing process, which is influenced by a number of factors, both internal and external to an organisation. A case study approach which consisted of four medium-sized manufacturing organisations in New Zealand was employed. Data was collected by way of in-depth interviews, direct observation of people and the organisations and a review of documentation. The study focused on those processes and contextual factors which influenced the method of implementation employed and which also served to constrain or facilitate the TQM implementation process. The interpretation of these processes and factors was informed by theories and concepts relating to TQM, implementation and organisational change. The study suggested that TQM implementation has a dynamic, iterative and cyclical nature which supports an emerging, processual perspective of organisational change, rather than the traditional rational and linear theory. Furthermore, it identified that factors such as resistance and a cursory knowledge of TQM acted to constrain the implementation process while the management of factors such as leadership, education and training and job enrichment determined whether they acted to constrain or facilitate the process. The study supports the need for a greater understanding to be had by those charged with the role of leading and managing the TQM implementation process. A greater appreciation of the cyclical characteristic of the change process and the holistic nature of TQM will enable management more effectively manage the processes inherent within the change process and which influence the organisational members accept and routinise the principles and procedures of TQM. The study concludes with a review of the methodology and then the managerial implications for future TQM implementation efforts are discussed. Finally, areas for future research are identified and presented.
Keywords: Organisational change; Total quality management (TQM); New Zealand